The Vocabulary Profile of UN (Ujian Nasional) Reading Texts of Senior High School - Atmadja, Andila (Institut Agama Islam Negeri (IAIN) Curup, 2020)
ABSTRACTThis the study was aimed at investigating vocabulary profile of English UN 2015 Reading Texts for Senior High School. Content analysis was used as a research method. The data were vocabularies which encountered within 14 reading texts. The instruments were Lewis (1997) divisions of lexical items adapted in Lakshmi (2012) and 1000-3000 new general service list by Browne and Coxhead (2013) within Vocab Profiler software inventing by Cobb (2009). The result showed that (1) There were four lexical items encountered in the UN 2015 Reading Text. They were: polywords, collocation, a fixed expression, and semi-fixed expression. (2) The most dominant of lexical items were encountered in the Reading Text is collocation with 145 words (60%), Polywords with 51 words (21%), Semi fixed expression with 38 words (16%) and the lowest was fixed expression with 7 words (3%). (3) There were 1067 words (88%) in the UN reading text were the extent of coverage level 1000-3000 NGSL and NAWL level by Browne and Coxhead. The conclusion was the teacher should teach the students about collocation and other word partnership in order to assist students to comprehend the English text better.